Counting of conjuntival cells by impression cytology in bovine and equine - Gonçalves, Roberto Calderon [UNESP]; Pereira, Eric de Castro [UNESP]; Flórez, Luis Mauricio Montoya; Pedraza, Francisco Javier; Chiacchio, Simone Biagio [UNESP]; Amorim, Rogério Martins [UNESP]; Borges, Alexandre Secorun [UNESP]; Rocha, Noeme Sousa [UNESP] (My University, 2012)
Impression cytology is a useful, non-invasive method of investigating the ocular surface. This method consists of applying a piece of filter paper to the conjunctiva. The samples obtained can comprise up to three cell layers, which are applied to a histological slide. This study aimed to evaluate the quality and quantity of cells in the bulbar conjunctivas of clinically healthy cattle and horses to facilitate the diagnosis of external eye diseases. To this end, samples of external ocular conjunctiva cells were collected from 15 adult cattle and 15 adult horses using the impression cytology method. For cytology, the samples were stained with Giemsa and Shorr. Two slides were prepared for each animal, one from the left eye and one from the right eye, and 800 cells were counted in total. For the statistical analysis, ANOVA was used with p<0.05 considered to be statistically significant. The analyses allowed for the comparison of the numbers of goblet cells, lymphocytes, and erythrocytes between the species and among the sampled animals. Impression cytology of the ocular surface was effective, and the technique was well accepted by cattle and horses.

A citologia por impressão é um método não invasivo útil para avaliar a superfície ocular. Consiste na aplicação de um fragmento de papel filtro sobre a conjuntiva. As amostras obtidas podem ter até três camadas de células e são distendidas em lâminas histológicas. O estudo teve como objetivo avaliar o padrão qualitativo e quantitativo das células da conjuntiva bulbar em bovinos e cavalos clinicamente saudáveis para facilitar o diagnóstico de doenças oculares externas. Para este fim, foram coletadas amostras de células externas da conjuntiva ocular pelo método de citologia de impressão de 15 bovinos e 15 equinos adultos. Para o exame citológico as amostras foram coradas por Giemsa e Shorr. Duas lâminas foram preparadas de cada animal, uma do olho esquerdo e outro do olho direito e foram contadas 800 células em total. Para a análise estatística, o ANOVA foi utilizado, foram considerados significativos os valores de p < 0,05. A análise permitiu estabelecer diferenças no numero de células caliciformes, linfócitos e eritrócitos entre espécies e animais. A citologia por impressão da conjuntiva bulbar foi eficaz na análise celular e foi bem aceita pelos bovinos e equinos.
Contagem de células conjuntivais por citologia de impressão em bovinos e equinos
Keywords: Cytology; Ophthalmology; Cattle; Horses; Citologia; Oftalmologia; Bovino; Equino